1971
DOI: 10.1113/expphysiol.1971.sp002110
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Fibre Counts and Retinal Ganglion Cell Counts During Development of Xenopus Laevis (Daudin)

Abstract: An account is given of the development of the optic nerve in Xenopus laevi8 (Daudin). The stages studied were 35, 38, 46, 52, 58, immediately post-metamorphosis (66), the juvenile of six months from metamorphosis and the adult. Fibre counts were made from complete electron micrograph montages for all the stages investigated including the adult. Corresponding ganglion cell counts were made from sections prepared by light microscopic histology from stage 46 upwards.The large increase found in the ganglion cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 7 publications
4
22
0
Order By: Relevance
“…S2A) confirmed that ON shortening did not interfere with the normal addition of new myelinated axons, known to occur throughout the lifespan of X. laevis (17), or with the continued addition of myelinating oligodendrocytes in the ON during this time (Fig. S2B).…”
Section: Significancesupporting
confidence: 53%
“…S2A) confirmed that ON shortening did not interfere with the normal addition of new myelinated axons, known to occur throughout the lifespan of X. laevis (17), or with the continued addition of myelinating oligodendrocytes in the ON during this time (Fig. S2B).…”
Section: Significancesupporting
confidence: 53%
“…However, whether this weak retinal specialisation is also functionally comparable, re mains unknown. Xenopus relies minimally on vision for survival and possesses only 52-59 x 104 fibres within its optic nerve [Wilson, 1971], Halophryne pos sesses 45 x 104 cells in the ganglion cell layer which is low in comparison to other teleosts, especially consid- Fig. 4.…”
Section: Australian Frogfishmentioning
confidence: 99%
“…It has been observed that the total number of fibres does not always correspond to the number of cells in the retina ganglion layer. In fact, the retinal ganglion cells are 27% more than the total number of fibres in the optic nerve in Xenopus laevis (Wilson, 1971), 22% more than in Bolitoglossa subpalmata, a plethodontid salamander (Linke et al, 1986), and over 39% more than in Notophtalmus viridescens (Ball & Dickson, 1983). The 'excess cells' are amacrine cells.…”
Section: Introductionmentioning
confidence: 99%
“…In X. laevis, it has been observed that the total number of fibres, at six months, is clearly greater than in the adult (58993 versus 51987), while the 3 396 myelinated fibres in the young animal increase to 7 235 in the adult, as a result of progressive myelinization (Wilson, 1971;Dunlop & Beazley, 1984). The diameter of the myelinated fibres is between 0.3 um and 3.0 um, while that of unmyelinated fibres is in the 0.1-2.0 pm range, with a prevalence of 0.2 um and 0.4 pm fibres.…”
Section: Introductionmentioning
confidence: 99%